(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Malaysia is a developing country rich in its culture and traditions dating back for centuries. The evolution of music in Malaysia, unnoticed by many, plays distinctive notes inspiring and transforming the paradigm shift of its people. Malaysian music transcends from melismatic, organum and minimalism, to the current progressive intervals, modulations and eclectic variations of form, structure, rhythm, chords and melodies. Vast social and economic developments change the appreciation of music in its representation by the transportation of musical essences through the delicate sensory motors of the human mind and body via sight and sound. The overall composition of this journal is to provide a thorough overview of the integration and of vocal singing and performance through the spectacle of music. Results, data, musical notations, facts and figures pertaining to this study shall be derived through books, articles, internet (reliable sources with citations) and interviews from industrialists and professionals. Conservation efforts through innovations would evidently furnish new and innovative musical ideas blending in through the inevitable influx of American/European and global new-age music. Unlike some neighboring countries that prioritize national interests, Malaysia welcomes innovations and new musical ideas. Nonetheless, the essence of the Malaysian heritage should never be compromised. To date, the diminishing factor of traditional music is rather disheartening.